Effect of the oral examinations in the national health screening program on preventive oral health care and treatments: a 19-year follow-up study - Hyeonjeong Go; Masae Kuboniwa; Youn-Hee Choi (BMC, 2024)
Abstract Objectives The national health screening (NHS) program in Korea serves as primary prevention by detecting oral diseases early for easier management. Dental scaling helps prevent oral disease and treat early periodontal disease. This study evaluated the effects of national oral examinations (NOE) in NHS on preventive oral hygiene care and dental treatments for a 19-year follow-up study. Methods We conducted a longitudinal observation of Korean adults ≥ 19 years between 2002 and 2003 from the Korean National Health Insurance Service (n = 4,669,107; men = 2,518,704; women = 2,150,403). The independent variable involved tracking the number of people who underwent the NOE recruited between 2002 and 2003 from 2002 to 2013. The dependent variables pertained to the number of dental scaling and the presence or absence of periodontal and dental caries treatments from 2014 to 2020. Results Individuals receiving 6 to 7 dental scaling during the follow-up exhibited an adjusted odds ratio (AOR) of 2.91 in the NOE-middle (3-4 times) and 3.30 in the NOE-high (5-6 times) (p < 0.001). The adjusted rate ratios were 1.69 in the NOE-middle and 1.77 in the NOE-high (p < 0.001). The AOR for periodontal treatment was 1.23 in the NOE-middle and NOE-high (p < 0.001). Conclusion Frequent NOEs lead to undergoing dental scaling and dental treatment, highlighting the importance of encouraging NOE attendance to improve population oral health. Expanding the scope of dental coverage for preventive intervention combined with NOE could help encourage greater participation and promote preventive oral healthcare.